Pengaruh Pemberian Pupuk Organik Kotoran Kambing Terhadap Pertumbuhan Dan Hasil Tanaman Seledri (Apium Graveolens L.) - I Gusti Ayu Diah Yuniti; I Made Suryana; Ramdhoani; Marthen Lende Wara (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Celery (Apium Graveolens L.) belongs to the important leaf vegetable group and has export value and is the second important spice plant after lettuce in terms of its popularity and value. Even today it has been used as a diet food and is always available throughout the year. But the cultivation of celery plants has not received serious attention. This is due to several factors, including the lack of public interest in celery cultivation. Therefore, research on the application of goat manure organic fertilizer on the growth and yield of celery (Apium Graveoluns L.) aims to determine the effect of giving goat manure organic fertilizer on the growth and yield of celery plants, and to determine the appropriate dose of goat manure organic fertilizer. the best effect on the growth and yield of celery plants. This study used a randomized block design (RBD) method with 6 treatments, with doses of goat manure organic fertilizer K0 (control), K1 12.5 grams, K2 25 grams, K3 37.5 grams, K4 50 grams, and K5 65.5 grams. Each treatment was repeated four times so that all treatments became 24. In testing the effect of organic goat manure on growth and yield of celery (Apium Graveolens L.) dose of 37.5 grams (K3) gave the best growth results for all parameters observed, namely plant height (cm), number of leaves (strands), root length (cm), root fresh weight (g), root dry weight (g), total plant fresh weight (g), total plant dry weight (g).